ARMS VERSUS BRACHIOLES: MORPHOGENETIC BASIS OF SIMILARITY AND DIFFERENCES IN FOOD-GATHERING APPENDAGES OF PELMATOZOAN ECHINODERMS - Rozhnov S.V. (My University, 2002)
The similarity in the skeleton model of the brachiolar food-gathering system of Blastozoa and the arm system of Crinozoa, including the apical growth with enantomorphous displacement of skeletal ele-ments, is explained by the primary organizing role of the radial ambulacral canals, which have the same branching model for ambulacral tentacles. The difference in the positions of brachioles and arms relative to the theca (exothecal and endothecal) is associated with the formation of the primary ambulacral tentacles directly on the body surface of the majority of Blastozoa, particularly, the closed vestibular cavity of crinoids. The supporting skeleton of brachioles arose as a branch of the plates covering the floor of the ambulacrum, if they were present, or formed similarly as a new formation outside the theca. The supporting skeleton of arms, brachials, developed as a result of the serial growth of plates positioned radially at the boundary of the aboral skeleton and tegmen formed due to the appearance of the vestibulum. The hypothesis of the inductive role of hydrocoel and its radial ambulacral appendages, which organize the arrangement of skeletal elements in the morphogenesis of echinoderms, enables the refinement of the principle of skeleton division into the axial and extraxial parts. The axial skeleton has a developmental model formed under the control of the radial ambu-lacral canals. Remaining skeleton is extraxial, subdivided into the symmetrized part arranged under direct or indirect organizing effect of the hydrocoel and unregulated, nonsymmetrized part, which is not connected initially with the influence of the hydrocoel.
Keywords: Echinodermata; Pelmatozoa; Crinoidea; ambulacral system; axial skeleton; extraxial skeleton; embryonic induction; arms